CONSTRUCTIVIST PARADIGM:LEARNING INNOVATION SKILLS IN ELT - Manda Negara, Irma; Rafika Nurhidayah; Kuncoro, Hendro (LPPM STBA Pontianak, 2025)
This study aimed to investigate the integration of LIS (4 C's) conducted by lecturers in ELT. A literature review based on the elaborate framework of the 21st century. The method used is a qualitative description with a constructivist approach to paradigm and phenomenology. The researcher arranges the data and classifies the data patterns during the data analysis process in order to determine which data best fits the study's goal. After that, assembling the context using the knowledge extracted from the organized data. Findings reveal that the lecturer implements several learning methods to encourage students' 4 C skills. Integrating 4 C's skills following the 21st-century requirements is the first step in preparing students to be admitted to the workforce and competed in an open global environment.